PERBEDAAN KEMAMPUAN MENGASUH ANAK BERDASARKAN STATUS MARITAL YANG DISANDANG OLEH PENGASUH DI TPA SE KECAMATAN TAMPAN PEKANBARU - Yani, Lora; Wilson, Wilson; Nurlita, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Based on the results of observations made, the authors see there are some phenomena that exist in most of the caregivers who are married to treat children with a loving but some are not too concerned with children, caregivers unmarried child does not sterilize milk bottles in the right way, low ability to care for children by a caregiver, caregivers do not understand the dangers of the substances in the landfill available toys such as lead (Pb), mercury (Hg), cadmium (Cd) and chromium (Cr).The purpose of this study was to determine the ability of parenting by caregivers who are married and single, and to find out how much differences parenting abilities are married with single caregivers in daycares Tampan Sub-district Pekanbaru City. The population are 26 people and saturation sampling technique that uses as many as 11 people caregivers who are married and 15 single caregivers. Data collection techniques in this regard because the data in the form of nominal data the method of data collection for the marital status from identity card respondents. As for the method of data collection using observations and interview on parenting ability. The data analysis technique used is the normality test, homogeneity, hypothesis testing and t test. From the research results obtained there is no significant difference between the ability of parenting by married caregivers and single caregivers in Tampan Sub-district Pekanbaru City. It can be viewed from the analysis of data obtained by the value of the results tcount obtained is 1.475 and the value of ttable = 2.064 at significance level [Î± = 0.05] (df = 24). Therefore it turns tcount <ttable or 1.475> 2.064 then H0 is accepted. So, there is no significant difference parenting abilities based on marital status are carried by caregivers.Keywords: parenting ability , caregiver marital status